Pancasila di Era Digital: Strategi Menguatkan Moral pada Generasi Z Melalui Media Sosial - Muhammad Fakhri Imam Saputra; Chelsea Azizah Putra Wijaya; Della Nurahma; Zaenul Slam (Lembaga Pengembangan Kinerja Dosen, 2025)
The digital era has brought significant changes on social interaction patterns, particularly through social media, which has became the primary means of communication for Generation Z. However, this phenomenon also poses moral challenges, such as the spread of hoaxes, cyberbullying, and the degradation of ethical values. This article examines strategies for strengthening the morals of Generation Z through Pancasila as the nation's fundamental ideology, utilizing social media as an educational and outreach tool. Using a qualitative approach through literature analysis and case studies, this study identifies strategies such as interactive digital campaigns, educational content based on Pancasila values, and collaboration between the government, educators, and influencers. The results indicate that the integration of Pancasila in social media content can increase moral awareness, build national identity, and prevent negative digital influences. The implication is that this strategy is not only relevant for Generation Z but also contributes to the formation of a digital society that is ethical and characterized by Pancasila.